DEVELOPMENT OF TEACHING MATERIALS FOR E-LEARNING-BASED STATISTICS MATERIALS ORIENTED TOWARDS THE MATHEMATICAL LITERACY ABILITY OF VOCATIONAL HIGH SCHOOL STUDENTS - In In Supianti; Poppy Yaniawati; Siti Zuraidah Md Osman; Jasem Al-Tamar; Niki Lestari (Jurnal Infinity, 2022)
The aim of this study is the development of teaching materials for statistical materials based on Edmodo-assisted e-learning and how they impact students' mathematical literacy skills. The method used is the Dick & Carey development model. The research population is class XII Catering, one of the Vocational High Schools in Bandung City, with a sample of class XII Catering 1. The instrument used a mathematical literacy test, validation sheet, student response questionnaire, and interview guidelines. The data collected were analyzed descriptively qualitatively through triangulation, Q-Cochran statistical test, and N-Gain test. The results of this study indicate that the design of teaching materials for statistical materials based on Edmodo-assisted e-learning is very feasible to use in learning mathematics. Furthermore, the results of the application of teaching materials have a positive effect on mathematical literacy skills with a reasonably good category. Therefore, teaching materials must further develop animation, use communicative language, and utilize the latest technology